2022
DOI: 10.21608/tsnj.2022.236061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Job Crafting Training Program on Staff Nurses Work Involvement at Mansoura University Hospital

Abstract: Background: Job crafting provides the opportunity to redesign nurses job towards their own strengths and interests for a better fit between their personal characteristics and the characteristics of their job that improve work involvement and performance. Aim: Investigate the effect of job crafting training program on staff nurses work involvement in I.C.U at Main Mansoura University Hospital Subjects and Methods: Design: A quasi-experimental design was utilized. Subjects: The subjects were included all staff n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
3
4
1
Order By: Relevance
“…This result was consistent with the findings of Chang et al, 10 who discovered that cognitive job crafting was lower than task and relational job crafting. This finding contradicts previous research, which found that relational crafting was the least important dimension among nurses 26,28 …”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This result was consistent with the findings of Chang et al, 10 who discovered that cognitive job crafting was lower than task and relational job crafting. This finding contradicts previous research, which found that relational crafting was the least important dimension among nurses 26,28 …”
Section: Discussioncontrasting
confidence: 99%
“…According to the findings of this study, most nurses had moderate perception levels for task, cognitive, and rational job crafting. This was consistent with the findings of Kassem and Ibrahim, 26 who discovered that most nurses had only a basic understanding of their jobs. Furthermore, contrary to the current study results, according to Baghdadi et al, 27 participating nurses demonstrated high levels of job crafting.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations